PENGEMBANGAN MONOPOLI ADIKSIMBA BERBANTUAN CARD SORT UNTUK SISWA KELAS V PADA MATERI MEMAHAMI TEKS NARASI - Anggraeni, Domas Cahya; Sismulyasih, Nugraheti (Universitas Negeri Makassar, 2024)
The purpose of this research is to assess the feasibility and effectiveness of using ADIKSIMBA monopoly media to enhance the fifth-grade students’ capacity to comprehend narrative text at SD Negeri Tinjomoyo 02 in learning Indonesian. The research employed research and development. The research involved the development of the ADIKSIMBA monopoly media assisted by card sort methods then the feasibility and effectiveness of using the media was tested on 28 fifth grade students of SDN Tinjomoyo 02. Non-test procedures were used to acquire study data, including interviews with fifth grade teachers, student and teacher needs questionnaires, and media feasibility validation questionnaires completed by material and media experts. Data was collected using test technique such as pretests and posttests to examine the effectiveness of monopolistic media. The data were analyzed using percentage test, t-test, and N-Gain test. The results indicated that the ADIKSIMBA monopoly media was found to be 93.75% (rated as